2016
DOI: 10.14393/bj-v32n3a2016-32829
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of fruits, diaspores, seeds, seedlings, and saplings of Syagrus coronata (Mart.) Becc.

Abstract: Licuri (Syagrus coronata (Mart.) Becc.) is an ornamental palm tree native of Brazil with great economic potential, because it provides raw material for manufacturing a wide range of products. The objective of this study was to assess the morphology of the fruits, diaspores, seeds, seedlings, and saplings of Syagrus coronata. The study was performed at the Laboratory of Seed Analysis (LSA) of the Federal Rural University of Pernambuco/Academic Unit of Garanhuns-PE, by using licuri fruits collected from the rura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
2
0
3
Order By: Relevance
“…(Magalhães et al, 2013) e Syagrus coronata Becc. (Santos-Moura et al, 2016). Em Bactridinae, somente Acrocomia apresenta germinação remota, em cuja espécie A. aculeata, tolerante à seca e concentrada no Cerrado brasileiro, foi identificada a formação de lígula (coleoptilo) (Nascimento e Souza et al, 2017), e corresponde ao gênero mais basal dentro da subtribo (Eiserhardt et al, 2011).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…(Magalhães et al, 2013) e Syagrus coronata Becc. (Santos-Moura et al, 2016). Em Bactridinae, somente Acrocomia apresenta germinação remota, em cuja espécie A. aculeata, tolerante à seca e concentrada no Cerrado brasileiro, foi identificada a formação de lígula (coleoptilo) (Nascimento e Souza et al, 2017), e corresponde ao gênero mais basal dentro da subtribo (Eiserhardt et al, 2011).…”
Section: Discussionunclassified
“…(Magalhães et al, 2013), Syagrus coronata Becc. (Santos-Moura et al, 2016) e Elaeis guineensis (Henderson, 2006) têm eofilos inteiros. De outro modo, os eofilos em Bactris podem ser bífidos ou raramente pinados (Dransfield et al, 2008), como em B. gasipaes (Silva et al, 2006) e B. maraja, que são bífidos.…”
Section: Discussionunclassified
“…Syagrus coronata (Mart) Becc is a palm of Arecaceae family, native and endemic to the Brazilian territory and it can be found in the Northeast (Pernambuco, Alagoas, Sergipe, Bahia State) and Southeast (Minas Gerais State) regions of Brazil (Soares, 2020). This palm grows in the arid conditions of the Brazilian "Caatinga" region with limited water availability and it provides the raw material for the manufacture of a wide range of products in the regions where agriculture is restricted (Santos Moura et al, 2016). This palm presents medium size, from 8 to 12 meters high and the diameter of the stipe between 20 and 40 centimeters (Gomes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Crepaldi et al (2001) reported a bunch with 1347 fruits with average length and diameter of 2 and 1.4 cm, respectively. The fruits are ovoid to ellipsoid drupes with fibrous epicarp, yellow to orange pulp, woody endocarp, and endosperm that changes from liquid to solid as the kernel mature (Gomes et al, 2018;Santos Moura et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos sobre morfologia de sementes e plântulas são essenciais para fornecer dados e padrões que possibilitem o reconhecimento de uma espécie em campo nos estádios iniciais do seu desenvolvimento (OLIVEIRA et al, 2014), contribuindo para a estudos de regeneração natural (SANTOS-MOURA et al, 2016), auxiliando em estudos ecológicos e taxonômicos (KELLERMANN et al, 2016) e, além disso, possibilitando o melhor conhecimento de espécies exóticas potenciais para a ornamentação e arborização urbana. Desta forma, trabalhos sobre morfologia tem merecido atenção como parte de estudos morfoanatômicos, ampliando o conhecimento sobre determinada espécie ou grupamento sistemático de plantas, buscando o reconhecimento de sementes e plântulas (OLIVEIRA, 1993).…”
Section: Introductionunclassified